INFLUENCE OF POWDER PARTICLE SIZES OF POROUS MATERIALS ON REDUCING THE AERODYNAMIC NOISE LEVEL - L. P. Pilinevich; M. V. Tumilovich; A. G. Kravtsov; D. M. Rumyantsev; K. V. Grib (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
One of the main means of reducing aerodynamic noise is the use of silencers, which can be made of various porous materials, depending on the specific operating conditions. The aim of the work is to study the dependence of the noise reduction on the characteristics of porous permeable materials (PPM) obtained by vibration molding from metal powders. Such PPMs have a wide range of porosity, high permeability, mechanical strength, provide the ability to work in a wide temperature range, high corrosion resistance, and therefore find more and more widespread application in practice. When designing silencers, their pore size, permeability, mechanical strength, cost, and the chemical composition of the material are taken into account. Basic research methods – determination of noise level, powder particle size, permeability coefficient, pore size. Vibration molding of PPM samples for experimental studies was carried out on a ВЭДС 10-1А vibration bench with vibration parameters that ensured the maximum bulk density of the powder in the mold (acceleration 10 m/s2, frequency 500 Hz). Main results – the dependence of the noise reduction value on the PPM characteristics obtained by the method of vibration molding of metal powders of various grades of various particle size distribution was studied. It has been shown that the most effective damping is provided by PPM from spherical bronze powder of the БрОФ10-1 grade with particle sizes of 350–400 microns, which provides at the same time a combination of a high level of noise reduction and high permeability to air or gas. It was found that the thickness of the muff significantly affects the efficiency of noise suppression, while the minimum thickness of the muff, which provides a sufficiently high degree of noise reduction, is about 3.5 mm, therefore it is not practical to increase the thickness of the muffler material above this value.